2015
DOI: 10.1016/j.ijid.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors, and impact on clinical outcome of extended-spectrum beta-lactamase-producing Escherichia coli bacteraemia: a five-year study

Abstract: The prevalence of ESBL-EC bacteraemia has been increasing dramatically. Previous colonization with ESBL-EC was a strong risk factor for ESBL-EC bacteraemia. More inadequate initial antimicrobial therapy was noted in the ESBL-EC group, but mortality and length of hospital stay were not significantly different from those of patients with non-ESBL-EC bacteraemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
61
4
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 19 publications
8
61
4
1
Order By: Relevance
“…Our study also demonstrated a significant association between previous antibiotic use and CTXNS-En bacteremia in the univariate analysis. Prior isolation of CTXNS-En also appears to be a potent risk factor [4, 6, 24], as shown in our study. These common risk factors found in both previous studies and our study may help to identify patients with CTXNS-En bacteremia.…”
Section: Discussionsupporting
confidence: 75%
“…Our study also demonstrated a significant association between previous antibiotic use and CTXNS-En bacteremia in the univariate analysis. Prior isolation of CTXNS-En also appears to be a potent risk factor [4, 6, 24], as shown in our study. These common risk factors found in both previous studies and our study may help to identify patients with CTXNS-En bacteremia.…”
Section: Discussionsupporting
confidence: 75%
“…Not surprisingly, risk factors and exposures associated with antimicrobial resistance in this study were largely consistent with previous reports [28][29][30][31][32][33][34][35]. The most important independent risk factors for both hospital and community acquisition of all three resistant bacteria were hospital prevalence of the resistant pathogen, admission source, and previous hospital admission within the prior 6 months [28][29][30][32][33][34][35]. All three of these factors capture time at risk in healthcare facilities among patient populations predisposed to infection by antibiotic-resistant pathogens [28][29][30][31][32][33][34][35] and highlight the importance of understanding the prevalence of a given antibiotic-resistant phenotype in an institution.…”
Section: -Gcr Mdrpsupporting
confidence: 92%
“…Using the Premier Hospital database, which included 124,068 hospital admissions from approximately 160 institutions that contributed microbiology data during the period from January 1, 2011, to October 1, 2015, we first identified the infection-, patient-, and hospital-level risk factors that increase the probability of having an infection due to 3GC-R, CRE, or MDRP. Not surprisingly, risk factors and exposures associated with antimicrobial resistance in this study were largely consistent with previous reports [28][29][30][31][32][33][34][35]. The most important independent risk factors for both hospital and community acquisition of all three resistant bacteria were hospital prevalence of the resistant pathogen, admission source, and previous hospital admission within the prior 6 months [28][29][30][32][33][34][35].…”
Section: -Gcr Mdrpsupporting
confidence: 91%
See 2 more Smart Citations